Fundamentals of Entrepreneurship (ENT 300) : Typo (Cotton On Group Co.) / Nur A’inaa Izzati Nazarihan … [et al.]. - Nazarihan, Nur A’inaa Izzati; Jamel, Mohd Shafiq Aima; Pathe, Khuhaimy (2018)
“Don’t quit,” is the quote that we keep on chanting in our mind when doing this case study. As long as we do not quit, we can get the job done. The company that we research is Typo. Typo sells gifts, stationeries, travel accessories and other daily necessities such as metal waterbottles and tumblers. The type of concept Typo has is new in Sarawak. None of the company or the store has the same concept in Sarawak before Typo company open their branch in here. Typo store has a cool nature and a unique aura that can attract customers to come to their store.